PENERAPAN MODEL COOPERATIVE TYPE TALKING STICK UNTUK MENGKAJI SELF-EFFICACY DAN PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS - Lenny Nurlatifah (Universitas Islam Nusantara, 2022)
This research is motivated by the low ability of understanding and self-efficacy of students. One alternative is to apply Cooperative Type Talking Stick learning. The purpose of this study was to determine self-efficacy and increase students' understanding ability using the Cooperative Type Talking Stick model with students who used the Discovery Learning model. The research method used was a quasi-experimental method, with a pretest-posttest control group design research design. The study was conducted at one of the State Junior High Schools in Bandung Regency, with the sample of students in class VII-A as an experimental class and class VII-B as a control class. The experimental class uses the Cooperative Type Talking Stick model, while the control class uses the Discovery Learning model. The instrument used was a self-efficacy questionnaire, a mathematical understanding ability test, and an observation sheet of educator activity. The results of the study were analyzed using two mean differences (t-test). Based on the analysis results, it can be concluded that the self-efficacy of students who use the Cooperative Type Talking Stick model and students who use the Discovery Learning model, both have very good self-efficacy qualifications. While increasing students' mathematical understanding ability using the Cooperative Type Talking Stick model is better than students using the Discovery Learning model.